Evaluation of chemical insecticides against Fall Armyworm, Spodoptera frugiperda (J. E. Smith) in maize - Bajracharya, Ajaya Shree Ratna; Bhat, Binu (Journal of Nepal Agricultural Research Council, 2024)
Fall armyworm, Spodoptera frugiperda is an invasive insect pest of maize in plains and hills of Nepal causing serious damage in summer as well as winter maize production. Field experiments were conducted in Randomized Complete Block Design (RCBD) to evaluate five chemical insecticides against S. frugiperda at National Entomology Research Center, Khumaltar, Lalitpur during 2021 and 2022. On the basis of percent plant with live larvae infestation, damage symptoms and damage score, Spinosad 45% SC, Spinetoram 11.7% SC and Chlorantraniliprole 18.5% SC were found consistently superior among the treatments. Average percent plant infestation with live larvae was recorded 0 to 3.81 percent whereas, percent plant with FAW damage symptoms was recorded 0 to 5.72 percent on Spinosad, Spinetoram and Chlorantraniliprole treated plots. Statistically, cocktail insecticide Chlorpyrifos 50% + Cypermethrin 5% EC was also found effective in comparison to control and average percent plant with live larvae and damage symptoms were recorded 14.82 to 31.48 percent and 4.74 to 46.29 percent, respectively. Statistically, Azadirachtin 0.15% was also found effective as compared to control, however, percent plant infestation was recorded as high as 91.57 percent. Spinosad, Spinetoram and Chlorantraniliprole can be judiciously utilized for chemical management of fall armyworm in Nepal.